PENGARUH LIMBAH ABU PEMBAKARAN BIOMASSA KELAPA SAWIT TERHADAP SIFAT-SIFAT FISIKA DAN MEKANIK HIGH IMPACT POLYSTYRENE (Jurnal Teknik Kimia USU, 2015)
This study aims was to determine the effect of palm oil fuel ash (POFA) composite as filler on the physical and mechanical properties of high impact polystyrene (HIPS) composites. The research methodology included preparation of raw materials, treatment POFA (hydration process of POFA), mixing using tumbler and then extruder, molding composite specimens, and testing. The variables used were weight ratio of HIPS with 140 mesh POFA at 95/5; 92.5/7.5; 90/10. The composites were tested by Fourier Transform Infrared (FTIR), ash content, specific gravity, tensile strength, elongation at break, impact strength, hardness test, and Scanning Electron Microscopy (SEM). The results of FTIR characterization shows the formation of –OH bonding that was suspected as Si-OH or Si-hydrat. Results of physical and mechanical properties of the composites shows that increase of the filler composition in HIPS-POFA composites until the ratio of 90/10, increase the specific gravity to 7.2% of the original, tensile strength did not change significantly to 28.4 MPa, elongation at break decreased to 2.7%, impact strength decreased to 3.183 KJ/m2, and the hardness increased to 110.5, and Scanning Electron Microscopy (SEM) test show the transformation of POFA structure on treated POFA and intercalation between the matrix and POFA.